Resident Perceptions of Competency and Comfort Before and After Telemedicine-ICU Implementation. Issue 6 (June 2018) - Summe, Alexa; Foor, Laura; Hoeck, Lauren; Campbell, Kristen; Boyd, Mark; Barnes, Mary Ann
Abstract : Objectives: The purpose of this study was to examine the impact telemedicine in the intensive care unit (ICU) has on the competency, satisfaction, and education of resident physicians. Methods: Telemedicine in the ICU was implemented in 2014 at a community hospital with 24 family medicine residents. Comfort with the performance of various common procedures; management of major medical diseases in the ICU; and level of comfort, attitudes, and satisfaction in work relationships with various staff members in the ICU were assessed before and 1 year after the telemedicine implementation. This was done by the residents' respective training year and by all year groups combined. The Likert scores for each category were averaged by year group and by the three year groups combined, and these averages were compared pre- and posttelemedicine implementation using the t test method. Results: All of the residents in the program participated voluntarily in the study, a 100% response rate. The results showed significant positive effects on resident education and satisfaction among ICU nurses and residents after the implementation of telemedicine-ICU. There were negative effects on residents' learning opportunities with the family medicine attending physicians, feelings of being a valued team member, and comfort with ventilator management. Conclusions: Telemedicine-ICU implementation had mixed effects on residents' perceptions of their ICU experience and training. Further studies should be conducted to assess how to maximize resident training in this setting. Abstract : Twenty-four-hour physician coverage in the intensive care unit (ICU) can be achieved with telemedicine. The effects of this coverage on resident education has not been well studied. The authors evaluated resident perception and comfort in patient care in the ICU before and after the implementation of telemedicine-ICU coverage. The results showed significant positive effects on resident education and satisfaction among ICU nurses and residents after the implementation of telemedicine ICU. There were negative effects on residents' learning opportunities with the family medicine attending physicians, feelings of being a valued team member, and comfort with ventilator management.Supplemental digital content is available in the text.